Assessment of corporate management practices in public universities in Kenya - Waswa, Fuchaka; Ombuki, Charles; Migosi, Joash; Metet, Joseph (Academic Journals, 2013)
In order to continue attracting and retaining high-class intellectual power and hence guarantee quality service delivery, public university management will need to change and adjust in line with increasing local democratisation and globalisation pressures. Scenarios that depict participatory decision-making and respect of divergent viewpoints will have to characterize the relationships among all stakeholders in the routine operations of universities. The purpose of this study was to assess the Corporate Management Practices in Public Universities in Kenya from the academic staff’s perspective. A likertscale approach based on 19 selected items in total quality management (TQM) was used for data collection from a random sample of 45 academic staff drawn from public Universities from August to September 2011. Findings show that university academic staff are generally marginalised when it comes to decision-making even on issues that directly affect them. Subtle top-down management approach is still rife and impacts negatively on service delivery. Deliberate efforts are needed to adopt a people-centred management system built on the tenets of mutual trust, respect and intellectual cum professional symbiosis in pursuit of sustainable quality assurance.
Keywords: Academic staff; TQM, Kenya